Experimental investigation of the tilt angle of turbulent structures in the core of fusion plasmas. (5th June 2019) - Pinzón, J.R.; Happel, T.; Hennequin, P.; Angioni, C.; Estrada, T.; Lebschy, A.; Stroth, U.
Abstract: The tilt angle of turbulent structures stands for the anisotropy of turbulence which is essential for understanding the dynamics of magnetized plasmas. It is a quantity predicted by theory and simulations, that provides information on the interplay between turbulence, micro-instabilities and plasma flows. A new method for measuring the tilt angle of turbulent structures in the core region of fusion plasmas using Doppler reflectometry is presented. First measurements of this type on the ASDEX Upgrade tokamak have shown a significant difference of tilt angle for different plasma conditions. The dominance of sheared flows in determining the structure tilt is experimentally demonstrated for different turbulence regimes.